العــنـف السياســي (دراسة نفسية) - الحصناوي, سعد عبد الزهرة; بريسم, علي عبد الحسين (Journal of College of Education, 2018)
the  present  study  highlights  one  of  the most  significant topics  in the  field of psychology, namely  political psychology . the   study  gives  the reader  a  clear  and  simplified vision of  political psychology  . the   study  also sheds  light upon political  violence in Iraq in terms of causes and means of treatment . the   study  includes  the following  topics :1-Definition of  political  violence .-introduction-movement, direction and types  of  political  violence .2-Distinction between  political  violence  and other  related  terms  .- political  violence  and political  terrorism .- political  violence  and political   conflict .- political  violence  and political  instability .3- Political  violence  Theories .-Culture  violence  theory .- Relative  deprivation  theory .-Balance  of  power  theory .-Theory of  political  for  political  violence  .-Rational choice theory .4-means of treatment of political  violence  in Iraq . the researcher  presents his own view on political violence  in Iraq in the  light of  what has been dealt with.